Foraminiferal detoxification breakdown induced by fatal levels of TiO2 nanoparticles - Inagaki, Yuka; Ishitani, Yoshiyuki; Tame, Akihiro; Uematsu, Katsuyuki; Tomioka, Naotaka; Ushikubo, Takayuki; Ujiié, Yurika (Frontiers in Marine Science, 2024)
The increase discharge of titanium dioxide (TiO2) nanoparticles, derived from engineered material waste, exerts a detrimental impact on both the marine ecosystem and public health. The cytotoxicity of TiO2 nanoparticles on marine organisms should be imperatively understood to tackle the urgent concern for the well-being of marine life. Various concentrations of TiO2 nanoparticles have proven to reach fatal levels in aquatic organisms, requiring a deeper exploration of cytotoxicity. Notably, certain benthic foraminifers, such as Ammonia veneta, have been identified as capable of incorporating TiO2 nanoparticles into vesicles. However, these organisms exhibit a detoxification mechanism through exocytosis, as indicated by previous transcriptomic inferences. This presents the advantage of assessing the tolerance of foraminifers to TiO2 nanoparticles as pollutants and investigating the long-term effects of cytotoxicity. In this study, we scrutinized the distribution of TiO2 nanoparticles within cells and the growth rates of individuals in seawater media containing 1, 5, 10, and 50 ppm TiO2 nanoparticles, comparing the results with a control group over a 5-week period, utilizing A. veneta stain. Transmission electron microscopy observations consistently revealed high concentrations of TiO2 nanoparticles in vesicles, and their expulsion from cells was evident even with exposure to 5 ppm TiO2 nanoparticles. Under the control and 1 ppm TiO2 conditions, foraminifers increased their cell volume by adding a calcification chamber to their tests every 1 or 2 days. However, the 5-week culturing experiments demonstrated that foraminifers gradually ceased growing under 5 ppm TiO2 nanoparticle exposure and exhibited no growth at > 10 ppm concentrations, despite an ample food supply. Consequently, these findings with A. veneta suggest that the foraminiferal detoxification system could be disrupted by concentrations exceeding 5 ppm of TiO2 nanoparticles. The toxic effect of TiO2 nanoparticles on meiofauna, such as benthic foraminifers, have been poorly understood, though these organisms play an important role in the marine ecosystem. Environmental accumulation of TiO2 nanoparticles on the coast has already exceeded twenty times more than foraminiferal detoxification level. Future studies focusing on toxic mechanism of TiO2 nanoparticles are crucial to prevent the breakdown of the marine ecosystem through accelerating discharge of TiO2 nanoparticles into the ocean.